2021
DOI: 10.15326/jcopdf.2020.0179
|View full text |Cite
|
Sign up to set email alerts
|

Improving Screening for Alpha-1 Antitrypsin Deficiency with Direct Testing in the Pulmonary Function Testing Laboratory

Abstract: For personal use only. Permission required for all other uses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Sequencing of the SERPINA1 gene in COPD patients was recently proposed as a possible tool for testing large cohorts [39]. Other ideas to improve AATD detection rates include family-based testing, detection of potential AATD patients by analysis of routinely collected electronic medical record (EMR) data, algorithmbased reminders within EMR software, and direct testing for AATD in pulmonary function testing laboratories [31,40]. As a recent study reported a profound lack of knowledge about rare respiratory diseases among paediatricians and medical students, increased training of (future) medical professionals by adding specific subjects to the medical curriculum might also improve the proportion of timely diagnosed AATD [41].…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing of the SERPINA1 gene in COPD patients was recently proposed as a possible tool for testing large cohorts [39]. Other ideas to improve AATD detection rates include family-based testing, detection of potential AATD patients by analysis of routinely collected electronic medical record (EMR) data, algorithmbased reminders within EMR software, and direct testing for AATD in pulmonary function testing laboratories [31,40]. As a recent study reported a profound lack of knowledge about rare respiratory diseases among paediatricians and medical students, increased training of (future) medical professionals by adding specific subjects to the medical curriculum might also improve the proportion of timely diagnosed AATD [41].…”
Section: Discussionmentioning
confidence: 99%
“… 3 This is often due to the fact that a confirmatory testing needs to be conducted in specialized centers. 13 , 14 Early identification of patients with AATD is recommended because delayed diagnosis worsens clinical status, including COPD-related symptoms. 15 …”
Section: Introductionmentioning
confidence: 99%
“…Despite the proven importance of case identification, early diagnosis of alpha1 antitrypsin deficiency (AATD) currently continues to be a challenge for clinicians and the health system [1]. The reasons for this lack of diagnosis are multifactorial and are related to the lack of systematic screening of potential patients and the need for a quick, simple method to confirm highly suspicious cases, among others [2][3][4].…”
Section: Introductionmentioning
confidence: 99%